(untitled) (Brazilian Journal of Radiation Sciences, 2018)
A radiological accident usually ends up bringing damage to society. The accident in Goiânia, which turns 30 years in 2017, could not be different. However, the polysemy of the term accident, which usually refers to malfeasance, can also lead to discussion of social issues, thus generating knowledge. In this context, the objective of this work was to present some contributions to the learning in the radioprotection area from this accident. In this case, a thematic workshop was held, together with the students of the Specialization Course in Radiological Protection and Security of Radioactive Sources, offered jointly by the Institute of Radioprotection and Dosimetry (IRD) and the International Atomic Energy Agency (IAEA), focusing on the performance of the IRD during the accident. To do this, some professors of the course made a statement about what was the greatest legacy of the accident for the radioprotection area. From the analysis of the speeches, the workshop was held to discuss the relevance of the accident, focusing on the survey of the scientific advances and lessons learned. Thus, it was sought to evidence the radiological accident as a learning tool in the field of nuclear science, opening space for discussions of a wider knowledge on ionizing radiation. In this way, it is not possible to deny the technological advance or to negate the learning originated from this tragedy in Brazilian soil, understanding that the investigations related to historical aspects of science end up leading to new implications in the teaching of sciences.